Use of fiber Bragg grating array and random decrement for damage detection in steel beam. (1st January 2016) - Elshafey, A.; Marzouk, H.; Gu, X.; Haddara, M.; Morsy, R.
Highlights: An array with 8 FBG sensors is surface mounted along the steel beam axis. An FFT analysis has been used to determine the frequency range that can be used to separate each mode shape. The natural frequencies, modal damping ratios, and mode shapes are extracted. RD is used to determine the natural frequencies and damping ratios, and to identify the existence of damage. Multichannel RD is used to determine the mode shapes to locate the damage. Abstract: A growing trend in the use of fiber Bragg grating array to detect structural damage has been observed in recent years. This paper describes the use of fiber Bragg grating optical sensors in an array to identify the location and assess the extent of damage on steel structures. A fiber optical sensing array with eight sensing elements has been designed, fabricated, and applied to measure the time history of strain at different points on a simply supported beam subjected to random loading. The wavelength shifts of the sensors are used to calculate the strain distribution along the beam. The random decrement at each point, for different modes, is extracted from the time history of the responses. The random decrements are compared at different damage ratios to an intact case to identify the existence of damage. Multichannel random decrement is applied to extract excited mode shapes. The mode shapes are then used to determine the location of the damage. The results show that the fiber optical sensor array is a reliable, fast, and accurate tool for the identification and localization of damage by using strain measurements.